Dukungan Sosial Dengan Burnout Pada Karyawan - Neni Triastuti; Walyono Walyono (Jurusan Psikologi FKIP Universitas Halu Oleo, 2023)
A company needs superiors and quality employees in carrying out their duties or obligations to make the company develop and advance the company. Without superiors and qualified employees, the company will be out of reach to develop and progress. This study aims to determine whether there is a relationship between Social Support and Burnout among PT. Independent Jone Innovation. The research approach used is a quantitative approach. The population in this study are employees of PT. Independent Jone Innovation. The sample in this study was 38 employees of PT. Independent Jone Innovation. Data collection techniques in this study used a questionnaire (questionnaire). Data analysis techniques used in this study are validity test, reliability test, normality test, and product moment correlation coefficient. Based on the results of the validity test on the social support and burnout variables, it was found that there were 8 items and 2 items dropped from each variable. Based on the calculation results of the Product Moment Correlation, it is known that there is a significant positive relationship between social support and the burnout variable. This shows that the positive contribution given by the social support variable with burnout is 20.5%.